2017
DOI: 10.1002/app.45091
|View full text |Cite
|
Sign up to set email alerts
|

Exploration on polypropylene carbonate polymer for gel polymer electrolyte preparation and dye‐sensitized solar cell application

Abstract: Gel polymer electrolytes (GPEs) with incorporation of poly(propylene) carbonate (PPC) polymer and different weight percentages of sodium iodide (NaI) salt are prepared. Ethylene carbonate (EC) and propylene carbonate (PC) are used as plasticizers. The maximum ionic conductivity of 2.01 mS cm 21 is achieved at room temperature. Temperature-dependent ionic conductivity study is performed. The GPEs are studied for structural properties using Fourier transform infrared (FTIR). The FTIR analysis confirms that compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Among the various electrolytes, the polymer electrolytes are the most extensively investigated systems. 10,76,[77][78][79] In recent years, the scientific community has turned its efforts in the direction of aqueous electrolytes; by means of DSSCs fabricated with water-based electrolytes, reduced costs, non-flammability, reduced volatility and improved environmental compatibility could be easily achieved. [80][81][82][83][84] Solid hole conductors capable of transporting charge and regenerating the dye, such as spiro-MeOTAD, can be used as charge mediators in DSSCs.…”
Section: Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…Among the various electrolytes, the polymer electrolytes are the most extensively investigated systems. 10,76,[77][78][79] In recent years, the scientific community has turned its efforts in the direction of aqueous electrolytes; by means of DSSCs fabricated with water-based electrolytes, reduced costs, non-flammability, reduced volatility and improved environmental compatibility could be easily achieved. [80][81][82][83][84] Solid hole conductors capable of transporting charge and regenerating the dye, such as spiro-MeOTAD, can be used as charge mediators in DSSCs.…”
Section: Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…We confirmed that with the addition of more salt into the host polymer, more free ions existed in the GPE samples, and this could lead to an enhancement in their σ. These results were in line with previous researchers’ results, where σ increased to a certain maximum range as the concentration of salt was increased …”
Section: Resultsmentioning
confidence: 99%
“…These results were in line with previous researchers' results, where σ increased to a certain maximum range as the concentration of salt was increased. 26,29 The σ values of the developed GPE samples at different temperatures, ranging from 30 to 100 C (from 303 to 373 K), were obtained, and the temperature-dependent σ was also studied. The values of σ of the GPE samples with different concentrations of NaI were recorded and are plotted in Figure 3.…”
Section: Eis Studies Of the Developed Gpe Samplesmentioning
confidence: 99%
“…Consequently, PPC‐based polymer electrolyte could be considered as a promising candidate for lithium‐ion battery application . Similarly, electrospun PPC/poly(vinylidene fluoride) and PPC/sodium iodide gel polymer electrolytes were used for LIBs application …”
Section: Biodegradability and Applicationsmentioning
confidence: 99%
“…[126] Similarly, electrospun PPC/poly(vinylidene fluoride) and PPC/ sodium iodide gel polymer electrolytes were used for LIBs application. [127,128] Poly(ethylene oxide) (PEO) is the most investigated solid polymer electrolyte (SPE) in LIBs. [129] However, it has a low ionic conductivity at room temperature, narrow electrochemical window, and poor mechanical properties which restrict its practical application in LIBs.…”
Section: Energy Applicationsmentioning
confidence: 99%